MODÉLISATION NUMERIQUE DE L’EFFET DES CHANGEMENTS CLIMATIQUES SUR LA NAPPE DE BERRECHID (MAROC) - Naïma El Assaoui; Fouad Amraoui; Bouabid El Mansouri (European Scientific Journal, ESJ, 2015)
Morocco takes part of the arid countries where groundwater resources play a vital role for their socio-economic development. The important increase in the water demand for various uses, coupled with the negative effects of the climate changes stresses increasly these groundwater reserves and weakens them. At the river watershed Bouregreg, both the quantity and the quality of groundwater are strongly decreased during last decades, especially at the Berrechid aquifer where the level of water, decreases continually in the piezometers during the period: 1980-2008, reaching 20 m in some places. The objective of this study is to analyze the impacts related to both the climate changes and the increase of water demand on the aquifer hydrodynamic to improve management and planning groundwater resources. Thus, a numerical model to simulate the aquifer hydrodynamics is proposed. It is based on MODFLOW, using GMS interface. The analysis of the impact of the climate changes on groundwater resources mobilized is based on Intergovernmental Panel one Climate Changes (IPCC) approach in terms of scenarios. The constraints imposed to the numerical model were based on three scenarios of IPCC, taking account of the aquifer’s recharge variation. The results show the continuing trend of declining groundwater levels with a variation between 1m and 25m.